WORK ORGANIZATION PEDIATRIC HOSPITAL IN CONDITIONS PANDEMICS OF NEW CORONAVIRUS INFECTION - Михаил Исаакович Ликстанов; Александр Владимирович Голомидов; Светлана Анатольевна Кузьменко; Вадим Гельевич Мозес; Кира Борисовна Мозес (The Publishing House Medicine and Enlightenment, 2021)
The article presents the basic principles of organizing inpatient pediatric care in the context of a coronavirus pandemic.